THE INFASTRUCTURE OF INCLUSION AND EXCLUSION: ACCESSING THE "PRIVATE INTERNET" FROM MAINLAND CHINA - Mai, Fan (AoIR Selected Papers of Internet Research, 2015)
There is a growing research literature on the technical aspects of internet censorship and circumvention, but the user’s experience with circumvention tools has received less attention. Empirical data about the use of circumvention tools, especially in countries that engage in substantial web filtering, is hard to find. Measuring the use of circumvention tools is inherently difficult given that the function of these tools is to protect the identity of the users. There are a few exceptions. Since 2007, researchers from the Berkman Center for Internet & Society at Harvard University have conducted in-depth evaluations of prominent filtering circumvention tools. Relying on data collected from website visits, search terms and self-reported information from the service providers, researchers at the Berkman Center estimated that less than 3% of internet users, in countries (including China) that engage in substantial filtering, use any circumvention tools. They also indicated that the actual number of the users is likely to be considerably less than this estimate (Roberts, Zuckerman, and Palfrey 2011). Comparing the estimate from the Berkman Center with my own findings, this question emerges: why is the adoption rate of proxy services is much higher among Western expatriates than among the general population of internet users in China? When studying the specific role of structure in affecting people’s consumption preferences, researchers have to consider the factors of availability of the media product in the market, and of users’ awareness enabled by the media environment (Webster 2009). This chapter first investigates the market that provides the VPN services, followed by a discussion of how expatriates learn about their circumvention options, especially the adoption of VPN service, in the Chinese context.